2021
DOI: 10.1177/21925682211035723
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Factors Associated With Chronic Opioid Use After Spine Surgery

Abstract: Study Design: Retrospective case control. Objectives: The purpose of the current study is to determine risk factors associated with chronic opioid use after spine surgery. Methods: In our single institution retrospective study, 1,299 patients undergoing elective spine surgery at a tertiary academic medical center between January 2010 and August 2017 were enrolled into a prospectively collected registry. Patients were dichotomized based on renewal of, or active opioid prescription at 3-mo and 12-mo postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…11 Risk factors for persistent opioid use after spine surgery include preoperative opioid use, depression, anxiety, chronic pain diagnoses, use of non-opioid pain medications, lower socioeconomic status, and younger age. 11,12 Careful consideration of these patient-level characteristics is warranted when formulating a multimodal pain regimen prior to surgery. In addition, extended intraoperative times and 4 or more levels of lumbar fusion further increase the likelihood of chronic opioid use after spine surgery, 12 and postoperative pain management regimens should be continuously modified to optimize non-opioid pain control as patients recover from surgery.…”
Section: Opioid Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Risk factors for persistent opioid use after spine surgery include preoperative opioid use, depression, anxiety, chronic pain diagnoses, use of non-opioid pain medications, lower socioeconomic status, and younger age. 11,12 Careful consideration of these patient-level characteristics is warranted when formulating a multimodal pain regimen prior to surgery. In addition, extended intraoperative times and 4 or more levels of lumbar fusion further increase the likelihood of chronic opioid use after spine surgery, 12 and postoperative pain management regimens should be continuously modified to optimize non-opioid pain control as patients recover from surgery.…”
Section: Opioid Managementmentioning
confidence: 99%
“…11,12 Careful consideration of these patient-level characteristics is warranted when formulating a multimodal pain regimen prior to surgery. In addition, extended intraoperative times and 4 or more levels of lumbar fusion further increase the likelihood of chronic opioid use after spine surgery, 12 and postoperative pain management regimens should be continuously modified to optimize non-opioid pain control as patients recover from surgery. Given the multitude of opioid-related adverse effects and the risks of new-onset depression and anxiety associated with chronic postoperative opioid use, 13 multimodal analgesic regimens optimizing non-opioid pain therapy have been proposed to reduce postoperative opioid requirements.…”
Section: Opioid Managementmentioning
confidence: 99%
“…Preoperative opioid use, preoperative depression and anxiety, smoking, Black race, more levels fused have been previously identified as risk factors for postoperative depression and anxiety and prolonged opioid use after spine surgery. 21,28-30 Based on the results of this study, patients with concomitant lower extremity arthritis are at 20% to nearly 34% increased relative risk of postoperative depression, anxiety, and prolonged opioid use, suggesting that this must be considered as a notable risk factor for postoperative mental health disorders and chronic opioid use.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to our findings, previous authors have identified a wide variation in discharge opioid amounts among spine surgery patients 7,9 and have identified patient-specific and perioperative factors associated with postoperative opioid prescriptions and use. For example, Pugely et al found that patients aged 50 years and older were associated with markedly higher 1-year opioid use after ACDF, 17 whereas Montgomery et al 18 found that younger age was associated with higher rates of opioid use at 3 months after spine surgery. The authors also identified associations between provider type and opioid prescription volumes after surgery, 9 with midlevel providers prescribing markedly higher discharge opioid volumes as compared with residents.…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies have also found associations between preoperative opioid use and increased postoperative opioid quantity and duration of use after spine surgery. 18,2022…”
Section: Discussionmentioning
confidence: 99%